Macroporous MgO monoliths prepared by sol–gel process with phase separation. Issue 14 (1st November 2016) - Li, Meiting; Zhou, Ningning; Luo, Xudong; Zhang, Guodong; Xie, Zhipeng; Xu, Linchong; Liu, Pengcheng
Abstract: Macroporous MgO monoliths were prepared with magnesium chloride (MgCl2 ·6H2 O) as a precursor, poly(ethylene oxide) (PEO) as a phase-separation inducer, and propylene oxide (PO) as a gelation agent via sol–gel processing. Based on the results of differential thermal analysis (TG-DTA), Fourier transform infrared (FT-IR) spectroscopy, X-ray diffractometry (XRD), and scanning electron microcopy (SEM), the effects of PEO addition on sinterability and microstructure of the monoliths were discussed. It was found that the amount of PEO should be within a certain range, within which the gel skeletons were gradually strengthened, three-dimensional interconnective macroporous structures were resulted and the porosity of the sintered specimens obviously increased with increasing PEO addition. Furthermore, the surfaces of MgO particles were coated with some cylindrical fibres ranged from 800 nm to 2 µm in diameter, and the quantity of the fibres is proportional to the PEO addition.